Introduction to research for midwives - Rees, Colin (Books for Midwives Press, 2003)
(Books for Midwives) Univ. of Wales College of Medicine, UK. Explores and explains research from the viewpoint of both those using it and those carrying it out. Written in simple language with clear examples. Demonstrates how quantitative and qualitative research projects are constructed and evaluated. Includes a glossary of research terms. Previous edition: c1997. Softcover.